Emigration of Ukrainian Scientists and Its Measurement - Yehorov, I. Yu. (Statistics of Ukraine, 2024)
The article is devoted to the problems of assessment of the volume of emigration of scientists from Ukraine. A brief analysis of the literature on migration problems is provided and estimates of the level of emigration of Ukrainian scientists during the period of independence are considered. Different approaches to calculations of the number of migrants are reviewed. Specific indicators of emigration, which were used in the 1990s and at the beginning of the XXI century, are analyzed. It is shown that the methods used by Ukrainian scholars in the past did not fully reflect the processes of scientific emigration. In the article, special attention is paid to the experience of other states regarding the return of migrant scientists to their home countries. It is stressed that the measures taken in this area by the governments of Taiwan and China may be applicable in Ukraine. Unlike Eastern European countries, these countries have managed to bring home a significant share of specialists from more developed countries, including, for example, the United States. It is proved that an important step for obtaining reliable data could be associated with the launch of specialized study in cooperation with migrant recipient countries, such as the CDH (Careers of Doctorate Holders) project implemented in OECD countries. The paper provides estimates of the real and potential losses of scientific personnel of Ukraine due to external migration, as a result of the war with the Russian Federation. The conclusions include propositions on how to improve migration statistics in the scientific sphere, in particular by introducing a General Register of scientists on a new basis. This, among other things, will allow specialists and decision-makers to have information about the processes of moving qualified personnel between research organizations, universities and sectors of the national economy. It is noted that it will be almost impossible to completely stop the emigration of scientists in the near future. Incentives to slow it down should include not only fairly obvious measures to raise wages and provide better working conditions (which is difficult to implement during the war and in the post-war times), but also stimulating the development of high-tech industries, which can give an impetus to research and development in the business sector of the economy. The directions of further research should be related to a more detailed study of the motives of migration among representatives of various scientific disciplines and an analysis of the consequences of the outflow of scientific personnel for the main sectors of the Ukrainian economy.